Diagnostic accuracy of doppler waveform pattern of hepatic veins in detection of cirrhosis in patient with hepatitis C taking histopathology as gold standard - Fida, Hina; Janan, Zubair; Noureen, Sumaira; Khan, Laila (International Journal of Pathology, 2025)
Background: Chronic hepatitis C infection frequently progresses to liver cirrhosis. Color Doppler ultrasound provides a non-invasive method to detect cirrhosis by identifying abnormal hepatic vein waveform patterns, offering an adjunct to invasive liver biopsy.Methods: This descriptive cross-sectional validation study was conducted at Department of Radiology, Mardan Medical Complex from January to September of 2025. A total of 96 patients aged between 18 and 60 years with chronic hepatitis C infection were included using non-probability consecutive sampling. Patients with esophageal varices, portal vein thrombosis, or hepatocellular cancer were excluded. Color Doppler ultrasound was performed using a 3.5 MHz transducer to assess hepatic venous waveform patterns. Abnormal waveforms were defined as biphasic (reduced phasicity) or monophasic (flat) patterns, compared to normal triphasic waveforms. Liver biopsy was performed under ultrasound guidance for histopathological confirmation. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated using histopathology as the gold standard.Results: The mean age was 50.16 ± 5.99 years with 53 (55.2%) males and 43 (44.8%) females. Mean duration of hepatitis C infection was 36.83 ± 15.04 months. Doppler ultrasound showed positive findings in 59 (61.5%) patients while histopathology confirmed cirrhosis in 54 (56.3%) cases. The diagnostic performance revealed sensitivity of 90.7% (95% CI: 79.7-96.9%), specificity of 76.2% (95% CI: 60.5-87.9%), positive predictive value of 83.0%, negative predictive value of 86.5%, and diagnostic accuracy of 84.3%. Significant associations were found in patients ≤50 years (p=0.03) and both genders (p<0.001), but not with HCV duration (p=0.12).Conclusion: Color Doppler ultrasound demonstrated high sensitivity and moderate specificity for detecting liver cirrhosis in hepatitis C patients. It represents a valuable first-line screening tool that can reduce reliance on invasive liver biopsies by approximately 76%, particularly beneficial in resource-limited settings where integration with elastography or serum biomarkers may enhance accuracy.